Keanekaragaman Makrozoobetos Sebagai Bioindikator Kualitas Perairan di Taman Hutan Raya Ngurah Rai, Bali - Sobari, Ari Isnen; Watiniasih, Ni Luh; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science, 2020)
Ngurah Rai Forest Park (Tahura) is one of the mangrove ecosystem areas in Bali which is an area of brackish forest type. Ngura Rai Tahura is based on administration in two city districts namely Badung and Denpasar. The Tahurah Ngurah Rai area is surrounded by housing, restaurants, hotels, malls, and shops as centers of community activities that have the potential to cause disruption to the balance of the aquatic ecosystem. The purpose of this research is to determine the diversity of macrozoobenthos and the condition of water quality in the mangrove ecosystem area in Tahura Ngurah Rai, Bali. This research uses a descriptive quantitative method that is exploratory in order to obtain facts of the conditions that exist through surveys in the field and identification in the laboratory. The sampling technique used was purposive sampling with transect quadrant measuring 1 x 1 m with teransek determination area of 5 m x 5 m. Sampling was carried out at four stations which included macrozoobenthos samples, measurement of water quality parameters (temperature, salinity, pH, DO, turbidity), and analysis of water-based substrates performed visually. Data from research conducted at three different locations in the Ngurah Rai Tahura mangrove ecosystem area found 55 species with a total abundance at station 1 6.68 ind / m 2 , station 2 4.52 ind / m 2 , station 3 3.55 ind / m 2 from the class Gastropoda, Crustacea, Bivalvia, and Polychaeta.. Diversity index at the three stations is classified as moderate level with water conditions that have experienced pressure or disturbance.